INFORMATION ON SOME LIPS (HEMIPTERA: APHIDIDAE) OF THE CENTRAL FERGANA REGION (Scientific journal of the Fergana State University, 2024)
Science knows 24 subfamilies, 510 genera and 5109 species belonging to the aphid family (Aphididae). Most aphids specialize in feeding on a specific type of plant, but some species can feed on hundreds of unrelated plants. Many authors have emphasized this (Dransfield and Brightwell, 2023; Singh and Singh, 2020; ). Taking these features into account, research work on the study of juices was carried out in the valley regions. This article presents new information on the study of aphidofauna.